FDG PET/CT of Cervical Gout With Spinal Cord Compression. (January 2020) - Emsen, Berivan; Fitoussi, Alexandre; Chalaye, Julia; Adam, Clovis; Itti, Emmanuel
Abstract : Abstract: We report FDG PET/CT images of a 63-year-old woman referred for characterization of osteolytic lesions of the cervical spine. This patient with chronic renal failure had a history of follicular thyroid carcinoma with undifferentiated cells, treated by a total thyroidectomy, completed by radioactive iodine in 2017. Because of cancer history, a FDG PET/CT was performed and showed multiple moderately hypermetabolic osteolytic lesions of the spine from C3 to T1, with joint erosion on CT. A laminectomy was performed for cervical spinal cord decompression and revealed a gouty tophus.